2016
DOI: 10.1002/ange.201604021
|View full text |Cite
|
Sign up to set email alerts
|

CuxCo1−xO Nanoparticles on Graphene Oxide as A Synergistic Catalyst for High‐Efficiency Hydrolysis of Ammonia–Borane

Abstract: Ammonia-borane (AB) is an excellent material for chemical storage of hydrogen. However,t he practical utilization of AB for production of hydrogen is hindered by the need of expensive noble metal-based catalysts.H ere,w er eport Cu x Co 1Àx Onanoparticles (NPs) facilely deposited on graphene oxide (GO) as alow-cost and high-performance catalyst for the hydrolysis of AB.T his hybrid catalyst exhibits an initial total turnover frequency (TOF) value of 70.0 (H 2 )m ol/(Cat-metal) mol·min, which is the highest TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Figure 3d reveals that the oxidized state of Cu in the Cu 2+ /GDYO nanosheets is consistent with the Cu 2+ ions in Cu(NO 3 ) 2 . [ 46 ] However, the Cu L ‐edge shifts to higher photon energies, further confirming that Cu 2+ ions receive electrons from the GDYO nanosheets.…”
Section: Resultsmentioning
confidence: 83%
“…Figure 3d reveals that the oxidized state of Cu in the Cu 2+ /GDYO nanosheets is consistent with the Cu 2+ ions in Cu(NO 3 ) 2 . [ 46 ] However, the Cu L ‐edge shifts to higher photon energies, further confirming that Cu 2+ ions receive electrons from the GDYO nanosheets.…”
Section: Resultsmentioning
confidence: 83%
“…Feng et al observed changes of the Cu state during AB hydrolysis using in situ XAFS, which showed that AB molecules interact with the catalyst rstly and water can approach both the catalyst and AB to attack the N-B bond. 61 Peng et al demonstrated the plausible AB hydrolysis mechanism using DFT calculations. 57 Thus, we show the possible mechanism of AB hydrolysis in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When Ni in +2 oxidation state substitutes W or Mo (in +4 oxidation state) in the carbide lattice, 81 an incumbent need to maintain the charge balance can trigger the Mo and W to attain a higher partial oxidation state, as observed from the XPS ( Figure S4a, b, S4b) and XANES spectra ( Figure S19a-b). XANES measurements at the Ni (K-edge, 8.33 keV), Mo (K-edge, 19.99 keV) and W (LIII edge, 10.207 keV) edges ( Figure S19a, S19b, and Figure 6) show a prominent increase in the white line intensity of the Mo/W centres upon Ni substitution ( Figure S19a, S19b) which is indicative of the increase in unoccupied states of the d-orbitals., 43,82 Interestingly, the Mo edge shows the appearance of an edge peak ( Figure S19b), corresponding to an 1s → 4 transition, presumably arising from a breaking in symmetry around the local coordination of Mo centres upon Ni substitution. The possibility of charge transfer between the electronically linked Ni & W/Mo ions is expected to optimize the electrochemical adsorption desorption processes resulting in enhanced electrocatalytic activity.…”
Section: Mechanistic Analysesmentioning
confidence: 99%